Enhancement of motor skill acquisition by intermittent theta burst stimulation: A pilot study - Kolbaşı, Esma Nur; Ersöz Hüseyinsinoğlu, Burcu; Özdemir, Zeynep; Bayraktaroğlu, Zübeyir; Soysal, Aysun (Springer, 2023)
Objective This study aims to analyze the effects of intermittent theta burst stimulation (iTBS) on motor skill acquisition of healthy subjects when applied on alternate days to ensure high adherence to treatment. Materials and methods Ten healthy participants (40-54 years) were included in the study. The control group (CG) (60% female) only received motor training (i.e., finger tapping task-FTTa), whereas the experimental group (EG) (100% female) received iTBS in addition to the motor training (every other day for 5 sessions). Cortical excitability measurements were taken with TMS. The correct sequences of the finger tapping test (FTTe) were recorded for behavioral analysis. Results While SICI was increased by 0.03 in EG, ICF was increased by 0.18 between pre-and post-treatment. On the other hand, CG had a lower ICF difference (MD: 0.05) and a higher SICI difference (MD: 0.21). There was no difference between EG and CG in FTTe at the end of the intervention (p > 0.05 for all variables), except for the increased number of correct sequences within the EG (p = 0.018). There was a significant difference in FTTa between EG and CG, in favor of EG (p = 0.042). The effect size was 0.62. Conclusion Although no difference was found in terms of cortical excitability and FTTe between the EG and CG at the end of the alternate-day treatment, it seemed like iTBS increased cortical facilitation further than CG. Furthermore, the number of correct sequences in FTTe and FTTa was significantly increased in EG, showing that intermittent iTBS might improve motor learning and performance.
Keywords: Memory and Learning Tests; Motor Cortex; Motor Evoked Potentials; Motor Skills; Transcranial Magnetic Stimulation